Shadow economy and public debt sustainability in Turkey - Burçin Yereli Ahmet; Seçilmiş Erdem İbrahim; Başaran Alparslan (Ekonomski Anali, 2007)
The aim of this study is to examine the relationship between the shadow economy and public debt in Turkey. We elaborate on the questions regarding the negative effects of shadow economy on the sustainability of public debt observing the estimates about the size of shadow economy in Turkey. In the light of some scholars’ estimates, we re-evaluate the macroeconomic situation of Turkey. At the core of the study, we discuss how the government borrowing policies would differ if the shadow economy was included into the legal system. In order to examine the effects of shadow economy on sustainability, we use various sustainability indicators. There is a significant difference observed between the calculations which take into account the volume of shadow economy as a share of economic system and those that exclude shadow economy as an exogenous variable. .